Fostering community empowerment and capacity building through tourism: perspectives from Dullstroom, South Africa. Issue 3 (27th May 2017) - Butler, Gareth
Abstract : This study observed tourism development in the popular South African destination of Dullstroom, Mpumalanga, and sought to identify the significant social benefits that have been fostered as a result. Dullstroom is synonymous with fly-fishing and is well-known throughout the country for its unique natural environment that is host to diverse flora and fauna. In the South African context, the impacts generated by tourism development on local communities have remained preoccupied with the economic benefits they deliver and rarely the important social gains that may also be developed. Between October 2012 and March 2013, a qualitative research methodology was developed to capture the views and experiences of 46 local employees (predominantly Non-white, South African females) and 16 owners or managers of local tourism-focused businesses. The findings reveal that tourism development has provided a number of positive impacts and that local community members encountered a number of benefits that ventured beyond economic factors. These benefits included empowerment through capacity building and the acquisition of positions that involved a high degree of responsibility, many of which would have been otherwise unobtainable but for the support of local tourism businesses. Others were afforded opportunities to pursue formal qualifications that enabled them to pursue dreams of senior positions or even new career paths beyond Dullstroom. The platforms that enabled these outcomes are discussed from the perspectives of both employers and employees in the local tourism economy.